2020
DOI: 10.2147/dmso.s257797
|View full text |Cite
|
Sign up to set email alerts
|

<p>Endoplasmic Reticulum (ER) Stress in Part Mediates Effects of Angiotensin II in Pancreatic Beta Cells</p>

Abstract: Introduction: The renin angiotensin aldosterone system (RAAS) is a hormone system known for its role in regulating blood pressure and fluid balance. Numerous RAAS inhibitors routinely prescribed for hypertension have also beneficial effects in type 2 diabetes (T2D) prevention. RAAS components are expressed locally in many tissues, including adipose tissue and pancreas, where they exert metabolic effects through RAAS bioactive hormone angiotensin II (Ang II). Pancreatic beta cells are specialized insulin-produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 60 publications
(98 reference statements)
1
12
0
Order By: Relevance
“…Importantly, cardiac and vascular cells exposed to Ang II presented ER stress activation characterized by an upregulation of ER stress markers. This effect was previously observed in adipocytes [ 66 ], in podocytes [ 67 ] and in pancreatic β cells [ 68 ]. We show for the first time that Ang II promotes ER stress activation in cardiac fibroblasts and VSMCs through mitochondrial oxidative stress production.…”
Section: Discussionsupporting
confidence: 76%
“…Importantly, cardiac and vascular cells exposed to Ang II presented ER stress activation characterized by an upregulation of ER stress markers. This effect was previously observed in adipocytes [ 66 ], in podocytes [ 67 ] and in pancreatic β cells [ 68 ]. We show for the first time that Ang II promotes ER stress activation in cardiac fibroblasts and VSMCs through mitochondrial oxidative stress production.…”
Section: Discussionsupporting
confidence: 76%
“…With some exceptions [ 301 , 302 , 303 , 304 ], several studies have shown the detrimental role of AGT-derived AngII on insulin release in vitro, ex vivo, and in vivo, both in animals and humans, which is at least partially mediated by reductions in proinsulin biosynthesis [ 305 , 306 , 307 , 308 , 309 , 310 , 311 , 312 ]. Concordantly, the inhibition of the RAS system has been demonstrated to be responsible for increased insulin biosynthesis and release in several obese, prediabetic, or diabetic models [ 313 , 314 , 315 , 316 , 317 , 318 , 319 , 320 , 321 ].…”
Section: Dysfunctional Adipose Tissue Secretome Affects β-Cell Functi...mentioning
confidence: 99%
“…Similarly, in a genetic murine model of obesity and diabetes, ACE2 overexpression in pancreas, improved glycemic control through Ang-(1-7), inducing both β-cell proliferation and apoptosis reduction[ 102 ]. As expected, similarly as a loss of ACE2, Ang II supplementation in beta cells significantly increased endoplasmic reticulum (ER) stress and inflammation leading to reduced insulin secretion whereas Ang II receptor blockade in beta cells reduced significantly ER stress and rescues insulin secretion[ 119 ].…”
Section: Covid-19 As a Risk Factor Of Diabetesmentioning
confidence: 66%